KEDUDUKAN DAN KEWENANGAN PEMERINTAH KECAMATAN DI KOTA DENPASAR MENURUT UNDANG – UNDANG NO.32 TAHUN 2004 DAN PERDA NO.9 TAHUN 2008 - Sudarmayasa, I Made; Puspawati, I Gusti Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
Indonesian is a sovereign independent state and local governments is an area whereintegritalnya. Therefore large and the number of government affairs, it is not possibleentirely in the care of its own by the central government based in Jakarta. In regard to thesetwo districts were formed in each district or city in Indonesia, position and authority districtsin the city of Denpasar as the local district or city. Where the purpose of the study is toexamine the status and authority of the district governments in accordance with thenormative method, which refers to Law 32 of 2004 on Regional Government and Regulation9 of 2008 concerning Organization and Work Denpasar District and Sub-District. Denpasarsubdistrict government authority under the Act 32 of 2004 wherein, Head in carrying outtheir duties in aid by the districts and accountable to the Regent and the Mayor through thesecretary. Implementation of Denpasar subdistrict government authority in relation to thegovernment of Denpasar where the implementation of the common tasks in the districtadministration. Form of guidance on kamtibmas village or village, community empowerment,fostering public welfare and development.
Keywords: Regional Autonomy, Government and Sub-district